The 10 best schools in the world (Journal of Parents and Teachers, 2026)
The desire to help children prepare themselves to fit in better with the world that awaits them is a global concern. Newsweek magazine has carried out an unusual investigation to identify the 10 best schools in the world. Below you can see the results and a brief overview of some of the key features of each school.
Keywords: The world's best schools